A retrospective study on 1592 consecutively performed operations in one private referral clinic. Part I: Early inflammation and early implant failures. (10th February 2017) - Antoun, Hadi; Karouni, Michel; Abitbol, Jérémy; Zouiten, Ons; Jemt, Torsten
Abstract: Background: Few large‐scale follow‐up studies are reported on routine implant treatment. Purpose: To report retrospective data on early inflammatory and early implant failures in a large number of routine patients at one private referral clinic. Materials and Methods: A total of 1017 patients were consecutively provided with 3082 implants with an anodized surface (Nobel Biocare AB) at 1592 implant operations between 2000 and 2011. All patients reported with mucosa inflammation and bone loss and/or implant failures to the first annual examination were identified. A logistic multivariate data analysis was performed to identify possible factors with an association to the two events. Results: Altogether 33 patients/operations presented early inflammation (2.1% operations). "History of periodontitis" (OR 3.91; 95% CI: 1.86‐8.21), "numbers of implants" (OR1.33; 95% CI:1.07‐1.67 per implant), "two stage surgical technique" (OR 3.70; 95% CI: 1.75‐7.85), and "lower jaw" treatment (OR 4.73; 95% CI: 2.12‐10.57) increased the risk for early mucositis with bone loss ( P < .05). Highest risk for early inflammation was observed for patients at an age of 50‐55 years at surgery ( P < .05). "Smoking habits" (OR 2.08; 95% CI: 1.06‐4.10) "Immediate implant placement" (OR 2.09; 95% CI: 1.23‐3.54), and "immediate grafting procedures" (OR 2.09; 95% CI: 1.04‐4.19) had a significant association to early implant failures ( P < .05). Furthermore, risk for an early failure decreased with 22% per year of inclusion (2000 >2011; OR 1.22; 95% CI;1.08‐1.39). Conclusion: History of periodontitis and two‐stage surgery protocols with bone grafts in the (posterior) lower jaw increased the risk for early inflammatory problems after surgery ( P < .05), with the highest risk for mid‐aged patients ( P < .05). Preventable factors related to the patient (smoking) and experience of surgeon showed to have a significant association to early implant failures in routine clinical practice ( P < .05).